PENENTUAN VARIASI KOMPOSISI DAN pH OPTIMUM ADSORBEN KITOSAN-Fe3O4 BERDASARKAN PERSEN PENYERAPAN ION Pb2+ - Lianasari, Ika Yekti; Koesnarpadi, Soerja; Pratiwi, Djihan Ryn; Munandar, Aris (Jurusan Kimia FMIPA UNMUL, 2023)
Previously, the synthesis of Chitosan-Fe3O4 adsorbent from magnetite (Fe3O4) made from ferrous ammonium sulfate (III) and ferrous ammonium sulfate (II) in a ratio of 3:1 was carried out. The adsorbent is adjusted with the ratio of magnetite and chitosan composition 1:1; 1:2 and 2:1 with the help of glutaraldehyde as a crosslinker. The results showed that the ratio of the ideal composition is 1:1 with % absorption that is 94.97% in 24 hour, and the optimum pH is obtained at pH 5 with % absorption of 92.18% for Pb2+ ions.